Prevalence and clinical implications of the rare arc of Bühler using computed tomography angiography and digital subtraction angiography: a systematic review and meta-analysis - Yan, Gaowu; Li, Yong; He, Suyu; Li, Hongwei; McClure, Morgan A.; Li, Qiang; Yang, Jifang; Wang, Hu; Zhao, Linwei; Fan, Xiaoping; Yan, Jing; Wu, Siyi; et al. (Frontiers in Medicine, 2025)
BackgroundKnowledge of the rare arc of Bühler (AOB) is limited but clinically important. At present, there is no publication of systematic review and meta-analysis on AOB in computed tomography angiography (CTA) and digital subtraction angiography (DSA) examinations.ObjectiveThe objective of this study was to evaluate the pooled prevalence and clinical implications of the AOB by using CTA and DSA examinations.MethodsThe PubMed, Web of Science, Scopus, Embase, Google Scholar, CBM, CNKI, WanFang, VIP, and Baidu Scholar databases were comprehensively searched for AOB-related literature. Stata 17.0 software was used to conduct the meta-analysis.ResultsEleven publications with 3,837 patients and 65 AOB cases were included. The pooled prevalence of AOB was 1.9% (95% confidence interval: 0.8–3.2%). CTA showed a pooled prevalence of AOB of 2.0% (95% confidence interval: 0.5–4.3%) and DSA showed a pooled prevalence of AOB of 1.8% (95% confidence interval: 0.5–3.9%).ConclusionAOB is a rare anatomical variant, with a pooled prevalence of 1.9% in the general population. General surgeons, vascular surgeons, and interventional radiologists should consider its existence when performing relevant abdominal procedures to avoid intraoperative difficulties, visceral organ ischemia or bleeding, and other complications.